A wear-resistant tire tread rubber and preparation method thereof

By combining the two-step modified white carbon black and composite filler, the problem of poor dispersion of white carbon black in the tread glue is solved, the anti-slip performance and wear resistance are improved, the rolling resistance is reduced, and the tread glue is enhanced. mechanical properties.

CN118812930BActive Publication Date: 2024-12-27WEIFANG SHUNFUCHANG RUBBER & PLASTIC CO LTD

Patent Information

Application Number
CN202411297542.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The dispersion of white carbon black in existing tread glue is not ideal, resulting in the inability to effectively improve the anti-slip performance and rolling resistance. At the same time, the vulcanization delay affects the tensile strength and wear resistance.

Method used

The modified white carbon black is prepared by a two-step modification method, and combined with nano-silicon carbide, nano-silicon nitride and graphite ball mill to form a composite filler. The dispersion and interface interaction of the filler are improved through ball milling and high-speed homogenization treatment, and combined with specific formulas and process steps to prepare the tread glue.

Benefits of technology

It significantly improves the anti-slip performance of the tread glue, reduces rolling resistance, and enhances tensile strength, tensile elongation and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a wear-resistant tire tread rubber and a preparation method thereof, belonging to the technical field of compositions of polymer compounds. The wear-resistant tire tread rubber comprises the following components, measured in parts by weight: 40-60 parts of natural rubber, 25-35 parts of styrene-butadiene rubber, 15-25 parts of isoprene rubber, 25-30 parts of modified white carbon black, 20-25 parts of composite filler, 15-20 parts of N330 carbon black, 2-3 parts of stearic acid, 1-2 parts of calcium oxide, 1-2 parts of zinc oxide, 2.5-3.5 parts of antioxidant 4020, 8-12 parts of environmentally friendly aromatic oil TDAE, 0.1-0.5 parts of polyimide, 1.2-2 parts of sulfur, 1-2 parts of accelerator TMTD, 0.5-1 parts of accelerator NOBS and 1-3 parts of anti-reversion agent HTS. The wear-resistant tire tread rubber prepared by the invention can improve the anti-wet skid capability of the tire using the tread rubber, reduce its rolling resistance, and enable the tread rubber to have higher wear resistance, tensile strength and elongation at break.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer compound compositions, and in particular relates to a wear-resistant tire tread rubber and a preparation method thereof. Background Art

[0002] The base material of tread rubber is rubber, but rubber material has large free volume, small intermolecular force, low glass transition temperature and amorphous high elastic state, so most rubber cannot be used without filler reinforcement. As a reinforcing filler, white carbon black can improve the anti-skid performance of tires and effectively reduce their rolling resistance, but white carbon black is very easy to agglomerate, and the interface between white carbon black and rubber matrix is ​​weak, so the reinforcement effect is not very ideal.

[0003] In the prior art, in order to improve the dispersibility of silica and enhance the compatibility of silica with the base material, the added silica is often modified by a silane coupling agent or a surfactant, or a silane coupling agent and a silica dispersant are added at the same time as the silica in the rubber refining process.

[0004] CN113929978B discloses a solid aircraft tire tread rubber and a preparation method thereof, wherein the raw material components include: natural rubber, white carbon black, silane coupling agent, white carbon black dispersant, N660 carbon black, etc. In the invention, white carbon black, silane coupling agent, and white carbon black dispersant are directly added in the mixing step. The silane coupling agent and the white carbon black dispersant can improve the dispersibility of white carbon black in the rubber matrix, but the directly added silane coupling agent has an unsatisfactory dispersing effect, resulting in poor dispersion stability of white carbon black and easy re-agglomeration, which cannot effectively improve the anti-skid performance of the tire using the tread rubber, nor can it effectively reduce its rolling resistance.

[0005] CN113502135B discloses a self-repairing rubber composition for tires and its preparation method, which uses a variety of materials such as reverse vulcanized rubber prepolymer, liquid isoprene, modified white carbon black, and tackifying resin. The modified white carbon black in the invention is hydrated silicon dioxide with the following groups modified and grafted on the surface: vinyl-triethoxysilane, dimethyldichlorosilane, polyethylene glycol-6000. The invention uses silane coupling agent or surfactant to modify white carbon black. Although this method improves the compatibility of white carbon black with the rubber matrix, it will cause the vulcanization of the rubber material to be delayed, resulting in a decrease in the tensile strength, elongation at break, and wear resistance of the tread rubber.

[0006] In summary, directly adding silane coupling agent will not produce ideal dispersion effect, and will easily cause silica to re-agglomerate, which cannot effectively improve the tire's anti-skid performance and reduce its rolling resistance. Using silica modified with silane coupling agent or surfactant will delay the vulcanization of rubber materials and affect the tensile strength, elongation at break and wear resistance of the tread rubber. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a wear-resistant tire tread rubber and a preparation method thereof, which can improve the anti-skid ability of the tire prepared using the tread rubber, reduce its rolling resistance, and make the tread rubber have higher wear resistance, tensile strength and elongation at break.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] A wear-resistant tire tread rubber comprises the following components, measured in parts by weight: 40-60 parts of natural rubber, 25-35 parts of styrene-butadiene rubber, 15-25 parts of isoprene rubber, 25-30 parts of modified white carbon black, 20-25 parts of composite filler, 15-20 parts of N330 carbon black, 2-3 parts of stearic acid, 1-2 parts of calcium oxide, 1-2 parts of zinc oxide, 2.5-3.5 parts of antioxidant 4020, 8-12 parts of environmentally friendly aromatic oil TDAE, 0.1-0.5 parts of polyimide, 1.2-2 parts of sulfur, 1-2 parts of accelerator TMTD, 0.5-1 parts of accelerator NOBS, and 1-3 parts of anti-reversion agent HTS.

[0010] The preparation method of the modified white carbon black includes primary modification and secondary modification;

[0011] The primary modification comprises: blending mercaptoalkanoic acid and ethanol to form a blending liquid A, blending white carbon black and ethanol to form a blending liquid B, adding the blending liquid B to an equal volume of the blending liquid A, stirring the mixture at 600-800 rpm for 4-6 hours, controlling the reaction temperature to 70-85° C., and standing the mixture for 10-12 hours after the stirring reaction, and then filtering, washing, and drying to obtain the primary modified white carbon black;

[0012] The mercaptoalkanoic acid is one of 3-mercaptopropionic acid, 4-mercaptobutyric acid, and 5-mercaptovaleric acid;

[0013] The mass ratio of mercaptoalkanoic acid to ethanol in the blended liquid A is (2-4): (10-40);

[0014] The mass ratio of white carbon black to ethanol in the blended liquid B is (10-15): (70-100);

[0015] In the first modification step, the washing liquid used for washing is ethanol, and the drying temperature is 50-70°C.

[0016] The secondary modification comprises adding tert-butyl peroxybenzoate and the primary modified white carbon black into a solution of styrene-butadiene rubber toluene, controlling the temperature to 85-100° C., ensuring that the reaction is carried out under a nitrogen atmosphere, stirring the reaction at 300-400 rpm for 6-10 hours, and then filtering, washing and drying to obtain the modified white carbon black;

[0017] The mass ratio of tert-butyl perbenzoate, primary modified white carbon black and solution polymerized styrene-butadiene rubber is (0.2-0.3): (12-16): (50-60);

[0018] The mass ratio of the solution polymerized styrene butadiene rubber to toluene in the solution polymerized styrene butadiene rubber toluene is (50-60): (400-600);

[0019] In the secondary modification step, the washing liquid used for washing is ethanol, and the drying temperature is 40-50°C.

[0020] The preparation method of the composite filler comprises preparing a mixed liquid, preparing a wet composite filler, and drying;

[0021] The mixed liquid is prepared by mixing nano silicon carbide, nano silicon nitride and graphite and loading them into a ball mill, adding ethanol-water mixed liquid for ball milling, controlling the ball-to-material ratio to (25-35):1, rotating speed to 200-320rpm, and time to 4-6h. After the ball milling is completed, ultrasonic treatment is performed for 10-20min, and the ultrasonic frequency is controlled to be 30-40kHz to obtain a mixed liquid;

[0022] The volume fraction of ethanol in the ethanol-water mixture is 60-80%;

[0023] The mass ratio of the nano silicon carbide, nano silicon nitride, graphite and ethanol-water mixed liquid is (0.3-0.5): (0.1-0.2): (3-5): (70-90).

[0024] The wet composite filler is prepared by dispersing N660 carbon black in an ethanol solution, homogenizing at a speed of 8000-12000 rpm for 10-20 min to obtain a carbon black solution, then adding the mixed liquid to the carbon black solution, homogenizing at a speed of 8000-12000 rpm for 12-18 min, and then filtering to remove the solvent to obtain a wet composite filler;

[0025] The mass ratio of N660 carbon black to ethanol in the carbon black solution is (5-9):100;

[0026] The mass ratio of the mixed liquid to the carbon black solution is (15-25):100.

[0027] The drying process includes drying the wet composite filler for 12-18 hours, controlling the drying temperature to be 55-70° C., and obtaining the composite filler.

[0028] The method for preparing the wear-resistant tire tread rubber of the present invention comprises the following steps: plasticizing, banburying, sheeting, and vulcanization;

[0029] Plastication: Plasticize the natural rubber, styrene-butadiene rubber and isoprene rubber in an open mixing mill at 56-62°C for 14-16 minutes, and then thinly pass through 3-5 times to obtain plasticized rubber.

[0030] Internal mixing: The initial temperature of the internal mixer is set to 65-75°C, and the initial speed is set to 25-30rpm. Then, the plasticized rubber is added to the internal mixer. After the plasticized rubber is added, the speed is adjusted to 45-60rpm. After mixing for 1-2 minutes, stearic acid, calcium oxide, zinc oxide, antioxidant 4020, environmentally friendly aromatic oil TDAE, and polyimide are added. After mixing for another 1-2 minutes, modified white carbon black, composite filler, and N330 carbon black are added in sequence. Mix for 12-14 minutes and discharge. After discharging, the material is parked and cooled for 10-12 hours to obtain the internal mixer.

[0031] Sheeting: Transfer the internal rubber mix to an open mixing mill, add sulfur, accelerator TMTD, accelerator NOBS, and anti-reversion agent HTS, and thin through 4-6 times. The processing temperature is controlled at 55-65°C. The sheet is parked and cooled for 14-18 hours to obtain the mixed rubber.

[0032] Vulcanization: Vulcanize the mixed rubber at 150-160°C for 20-25 minutes to obtain the tread rubber.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The wear-resistant tire tread rubber prepared by the present invention has excellent dynamic performance. The tire prepared by using the tread rubber has excellent anti-skid performance and low rolling resistance. The 0°C tanδ of the tread rubber of the present invention is 0.268-0.278, and the 60°C tanδ is 0.091-0.095.

[0035] (2) The wear-resistant tire tread rubber prepared by the present invention has good wear resistance and strength performance. The wear volume of the tread rubber Akron prepared by the present invention is 0.095-0.102cm 3 , tensile strength is 28.6-29.4MPa, and elongation at break is 658-670%. DETAILED DESCRIPTION

[0036] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0037] Example 1

[0038] A wear-resistant tire tread rubber, the raw material components are weighed according to the weight parts of raw materials in Table 1;

[0039] The method for preparing wear-resistant tire tread rubber comprises the following steps: plasticizing, banburying, sheeting, and vulcanization;

[0040] (1) Plasticizing

[0041] Natural rubber, styrene-butadiene rubber and isoprene rubber were plasticized in an open mill at 56°C for 16 minutes and then thinned three times to obtain a plasticized rubber.

[0042] (2) Secret refining

[0043] The initial temperature of the internal mixer was set to 65°C, and the initial speed was set to 25 rpm. Then the plasticized rubber was added to the internal mixer. After the plasticized rubber was added, the speed was adjusted to 45 rpm. After mixing for 2 minutes, stearic acid, calcium oxide, zinc oxide, antioxidant 4020, environmentally friendly aromatic oil TDAE, and polyimide were added. After mixing for another 1 minute, modified silica, composite filler, and N330 carbon black were added in sequence. The material was mixed for 12 minutes and discharged. After discharging, it was parked and cooled for 10 hours to obtain the internal mixer.

[0044] The preparation of the modified white carbon black comprises the following steps:

[0045] A. One-time modification

[0046] 3-Mercaptopropionic acid and ethanol (mass ratio of 2:10) were blended to prepare blend liquid A, and white carbon black and ethanol (mass ratio of 10:70) were blended to prepare blend liquid B. Blend liquid B was added to an equal volume of blend liquid A, and the mixture was stirred at 600 rpm for 6 hours. The reaction temperature was controlled to be 70°C. After stirring the reaction, the mixture was allowed to stand for 10 hours, and the filter cake was filtered out, which was then washed with ethanol 3 times and dried at 50°C to obtain a primary modified white carbon black.

[0047] B. Secondary modification

[0048] Tert-butyl peroxybenzoate and primary modified white carbon black were added to the styrene-butadiene rubber toluene solution under stirring conditions, the temperature was controlled at 85°C, and the reaction was carried out under a nitrogen atmosphere. After stirring at 300 rpm for 10 hours, a filter cake was obtained by suction filtration, which was then washed with ethanol for 3 times and dried at 40°C to obtain modified white carbon black.

[0049] The mass ratio of tert-butyl perbenzoate, primary modified white carbon black and solution polymerized styrene-butadiene rubber is 0.2:12:50;

[0050] The mass ratio of the solution polymerized styrene butadiene rubber to toluene in the solution polymerized styrene butadiene rubber toluene is 50:400.

[0051] The preparation of the composite filler comprises the following steps:

[0052] A. Preparation of mixed liquid

[0053] Nano silicon carbide, nano silicon nitride and graphite are mixed and loaded into a ball mill, and an ethanol-water mixture is added for ball milling. The ball-to-material ratio during ball milling is controlled to be 25:1, the rotation speed is 200 rpm, and the time is 6 hours. After the ball milling is completed, ultrasonic treatment is performed for 10 minutes, and the ultrasonic frequency is controlled to be 40 kHz to obtain a mixed liquid;

[0054] The mass ratio of the nano silicon carbide, nano silicon nitride, graphite, and ethanol-water mixture is 0.3:0.1:3:70;

[0055] The volume fraction of ethanol in the ethanol-water mixture is 60%.

[0056] B. Preparation of wet composite fillers

[0057] N660 carbon black is dispersed in an ethanol solution, and the mixture is homogenized at 8000 rpm for 20 min to obtain a carbon black solution. The mixed liquid is then added to the carbon black solution, and the mixture is homogenized at 8000 rpm for 18 min. The solvent is then removed by filtration to obtain a wet composite filler.

[0058] The mass ratio of the mixed liquid to the carbon black solution is 15:100;

[0059] The mass ratio of N660 carbon black to ethanol in the carbon black solution is 5:100.

[0060] C. Drying

[0061] The wet composite filler was dried for 12 hours, and the drying temperature was controlled at 70° C. to obtain a composite filler.

[0062] (3) Film production

[0063] The internal rubber mixture was transferred to an open mixing mill, sulfur, accelerator TMTD, accelerator NOBS, and anti-vulcanization reversion agent HTS were added, and the mixture was thinned through 4 times. The processing temperature was controlled at 65°C, and the sheets were parked and cooled for 18 hours to obtain a mixed rubber.

[0064] (4) Vulcanization

[0065] The mixed rubber was vulcanized at 150°C for 25 minutes to obtain a tread rubber.

[0066] Example 2

[0067] A wear-resistant tire tread rubber, the raw material components are weighed according to the weight parts of raw materials in Table 1;

[0068] The method for preparing wear-resistant tire tread rubber comprises the following steps: plasticizing, banburying, sheeting, and vulcanization;

[0069] (1) Plasticizing

[0070] The natural rubber, styrene-butadiene rubber and isoprene rubber were plasticized in an open mill at 60°C for 15 minutes and then thinned 4 times to obtain a plasticized rubber.

[0071] (2) Secret refining

[0072] The initial temperature of the internal mixer was set to 70°C, and the initial speed was set to 27rpm. Then the plasticized rubber was added to the internal mixer. After the plasticized rubber was added, the speed was adjusted to 50rpm. After mixing for 1.5min, stearic acid, calcium oxide, zinc oxide, antioxidant 4020, environmentally friendly aromatic oil TDAE, and polyimide were added. After mixing for another 1.5min, modified silica, composite filler, and N330 carbon black were added in sequence. The material was mixed for 13min and discharged. After discharging, it was parked for cooling for 11h to obtain the internal mixer.

[0073] The preparation of the modified white carbon black comprises the following steps:

[0074] A. One-time modification

[0075] 4-Mercaptobutyric acid and ethanol (mass ratio of 3:20) were blended to prepare blend liquid A, and white carbon black and ethanol (mass ratio of 12:80) were blended to prepare blend liquid B. Blend liquid B was added to an equal volume of blend liquid A, and the mixture was stirred at 700 rpm for 5 hours. The reaction temperature was controlled to be 75°C. After stirring the reaction, the mixture was allowed to stand for 11 hours, and the filter cake was filtered out, which was then washed with ethanol for 3 times and dried at 60°C to obtain a primary modified white carbon black.

[0076] B. Secondary modification

[0077] Tert-butyl peroxybenzoate and primary modified white carbon black were added to the styrene-butadiene rubber toluene solution under stirring conditions, the temperature was controlled at 90°C, and the reaction was carried out under a nitrogen atmosphere. After stirring at 350 rpm for 8 hours, a filter cake was obtained by suction filtration, which was then washed with ethanol for 3 times and dried at 45°C to obtain modified white carbon black.

[0078] The mass ratio of tert-butyl perbenzoate, primary modified white carbon black and solution polymerized styrene-butadiene rubber is 0.25:14:55;

[0079] The mass ratio of the solution polymerized styrene butadiene rubber to toluene in the solution polymerized styrene butadiene rubber toluene is 55:500.

[0080] The preparation of the composite filler comprises the following steps:

[0081] A. Preparation of mixed liquid

[0082] Nano silicon carbide, nano silicon nitride and graphite are mixed and loaded into a ball mill, and an ethanol-water mixture is added for ball milling. The ball-to-material ratio during ball milling is controlled to be 30:1, the rotation speed is 260 rpm, and the time is 5 hours. After the ball milling is completed, ultrasonic treatment is performed for 15 minutes, and the ultrasonic frequency is controlled to be 35 kHz to obtain a mixed liquid.

[0083] The volume fraction of ethanol in the ethanol-water mixture is 70%;

[0084] The mass ratio of the nano silicon carbide, nano silicon nitride, graphite and ethanol-water mixed liquid is 0.4:0.15:4:80.

[0085] B. Preparation of wet composite fillers

[0086] Dispersing N660 carbon black in an ethanol solution, homogenizing at 10000 rpm for 15 min to obtain a carbon black solution, then adding the mixed liquid to the carbon black solution, homogenizing at 10000 rpm for 15 min, and then filtering to remove the solvent to obtain a wet composite filler;

[0087] The mass ratio of N660 carbon black to ethanol in the carbon black solution is 7:100;

[0088] The mass ratio of the mixed liquid to the carbon black solution is 20:100.

[0089] C. Drying

[0090] The wet composite filler was dried for 15 hours, and the drying temperature was controlled at 60° C. to obtain a composite filler.

[0091] (3) Film production

[0092] The internal rubber mixture was transferred to an open mixing mill, sulfur, accelerator TMTD, accelerator NOBS, and anti-vulcanization reversion agent HTS were added, and the mixture was thinned through 5 times. The processing temperature was controlled at 60°C, and the sheets were parked and cooled for 16 hours to obtain a mixed rubber.

[0093] (4) Vulcanization

[0094] The rubber compound was vulcanized at 155°C for 22 minutes to obtain a tread rubber.

[0095] Example 3

[0096] A wear-resistant tire tread rubber, the raw material components are weighed according to the weight parts of raw materials in Table 1;

[0097] The method for preparing wear-resistant tire tread rubber comprises the following steps: plasticizing, banburying, sheeting, and vulcanization;

[0098] (1) Plasticizing

[0099] Natural rubber, styrene-butadiene rubber and isoprene rubber were plasticized in an open mill at 62°C for 14 minutes and then thinned through 5 times to obtain a plasticized rubber.

[0100] (2) Secret refining

[0101] The initial temperature of the internal mixer was set to 75°C, and the initial speed was set to 30 rpm. Then the plasticized rubber was added to the internal mixer. After the plasticized rubber was added, the speed was adjusted to 60 rpm. After mixing for 1 minute, stearic acid, calcium oxide, zinc oxide, antioxidant 4020, environmentally friendly aromatic oil TDAE, and polyimide were added. After mixing for another 2 minutes, modified silica, composite filler, and N330 carbon black were added in sequence. The material was mixed for 14 minutes and discharged. After discharging, it was parked for cooling for 12 hours to obtain the internal mixer.

[0102] The preparation of the modified white carbon black comprises the following steps:

[0103] A. One-time modification

[0104] 5-Mercaptovaleric acid and ethanol (mass ratio of 4:40) were blended to prepare blend liquid A, and white carbon black and ethanol (mass ratio of 15:100) were blended to prepare blend liquid B. Blend liquid B was added to an equal volume of blend liquid A, and the mixture was stirred at 800 rpm for 4 hours. The reaction temperature was controlled to be 85°C. After stirring the reaction, the mixture was allowed to stand for 12 hours, and the filter cake was filtered out, which was then washed with ethanol 4 times and dried at 70°C to obtain a primary modified white carbon black.

[0105] B. Secondary modification

[0106] Tert-butyl peroxybenzoate and primary modified white carbon black were added to the styrene-butadiene rubber toluene solution under stirring conditions, the temperature was controlled at 100°C, and the reaction was carried out under a nitrogen atmosphere. After stirring at 400 rpm for 6 hours, a filter cake was obtained by suction filtration, which was then washed with ethanol for 4 times and dried at 50°C to obtain modified white carbon black.

[0107] The mass ratio of tert-butyl perbenzoate, primary modified white carbon black and solution polymerized styrene-butadiene rubber is 0.3:16:60;

[0108] The mass ratio of the solution polymerized styrene butadiene rubber to toluene in the solution polymerized styrene butadiene rubber toluene is 60:600.

[0109] The preparation of the composite filler comprises the following steps:

[0110] A. Preparation of mixed liquid

[0111] Nano silicon carbide, nano silicon nitride and graphite are mixed and loaded into a ball mill, and an ethanol-water mixture is added for ball milling, the ball-to-material ratio during ball milling is controlled to be 35:1, the rotation speed is 320 rpm, and the time is 4 hours. After the ball milling is completed, ultrasonic treatment is performed for 20 minutes, and the ultrasonic frequency is controlled to be 30 kHz to obtain a mixed liquid;

[0112] The volume fraction of ethanol in the ethanol-water mixture is 80%;

[0113] The mass ratio of the nano silicon carbide, nano silicon nitride, graphite and ethanol-water mixed liquid is 0.5:0.2:5:90.

[0114] B. Preparation of wet composite fillers

[0115] N660 carbon black is dispersed in an ethanol solution, and the mixture is homogenized at 12000 rpm for 10 min to obtain a carbon black solution. The mixed liquid is then added to the carbon black solution, and the mixture is homogenized at 12000 rpm for 12 min. The solvent is then removed by filtration to obtain a wet composite filler.

[0116] The mass ratio of N660 carbon black to ethanol in the carbon black solution is 9:100;

[0117] The mass ratio of the mixed liquid to the carbon black solution is 25:100.

[0118] C. Drying

[0119] The wet composite filler was dried for 18 hours, and the drying temperature was controlled at 55° C. to obtain a composite filler.

[0120] (3) Film production

[0121] The internal rubber mixture was transferred to an open mixing mill, sulfur, accelerator TMTD, accelerator NOBS, and anti-vulcanization reversion agent HTS were added, and the mixture was thinned for 6 times. The processing temperature was controlled at 55°C, and the sheets were parked and cooled for 14 hours to obtain a mixed rubber.

[0122] (4) Vulcanization

[0123] The mixed rubber was vulcanized at 160°C for 20 minutes to obtain a tread rubber.

[0124] Comparative Example 1

[0125] Comparative Example 1 adopts the method for preparing the wear-resistant tire tread rubber described in Example 2, and the component formula is added according to the weight parts in Table 1. The difference is that in the mixing step, the preparation of modified silica is changed to:

[0126] The silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH570) and ethanol (mass ratio of 3:20) were blended to prepare blend liquid A, and white carbon black and ethanol (mass ratio of 12:80) were blended to prepare blend liquid B. Blend liquid B was added to an equal volume of blend liquid A, and the mixture was stirred at 700 rpm for 5 hours. The reaction temperature was controlled to be 75°C. After stirring the reaction, the mixture was allowed to stand for 11 hours, and the filter cake was filtered out, which was then washed with ethanol three times and dried at 60°C to obtain modified white carbon black.

[0127] Comparative Example 2

[0128] Comparative Example 2 adopts the method for preparing the wear-resistant tire tread rubber described in Example 2, and the component formula is added according to the weight parts in Table 1. The difference is that in the mixing step, the preparation of the composite filler is changed to:

[0129] Nano silicon carbide, nano silicon nitride, graphite and N660 carbon black (mass ratio of 0.4:0.15:4:80) were added into a mixer, mixed at 300 rpm for 30 minutes and then discharged to obtain a composite filler.

[0130] Comparative Example 3

[0131] Comparative Example 3 adopts the method for preparing the wear-resistant tire tread rubber described in Example 2, and the component formula is added according to the weight parts in Table 1. The difference is that in the mixing step, white carbon black is used instead of modified white carbon black.

[0132] Table 1 Tread rubber formula:

[0133]

[0134] The tread rubbers prepared in Comparative Examples 1-3 and Examples 1-3 were subjected to performance tests. The mechanical properties of the tread rubbers were tested according to GB / T528-2009. The test samples were cut into a specific dumbbell shape, the sample thickness was 2 mm, the clamp distance was 75 mm, the punctuation distance was 25 mm, and the stretching speed was 500 mm / min. The dynamic mechanical properties of the tread rubber were tested by temperature scanning using dynamic mechanical thermal analysis (DMTA). The temperature test scanning range was -10°C to 70°C, the heating rate was set to 5°C / min, the frequency was 10 Hz, and the strain was 0.20%. The wear resistance of the tread rubber was tested according to GBT1689-2014. The test results are shown in Table 2.

[0135] Table 2 Tread rubber properties:

[0136]

[0137] The loss factor of the tread rubber at different temperatures is tested to characterize the dynamic mechanical properties of the tread rubber. Under normal circumstances, the loss factor tanδ at 0℃ has a certain correlation with the anti-wet skid performance of the tread rubber. The higher the value, the better the anti-wet skid performance of the tread rubber; the loss factor tanδ at 60℃ has a certain correlation with the hysteresis loss of the tread rubber. The smaller the value, the smaller the hysteresis heat generation of the tread rubber and the smaller the rolling resistance. As can be seen from Table 2, the 0℃ tanδ of the tread rubber of Comparative Example 1 and Comparative Example 3 is lower than that of Example 2, and the 60℃ tanδ is higher than that of Example 2. The tensile strength, elongation at break and wear resistance of the tread rubber of Comparative Example 1 and Comparative Example 3 are also slightly lower than those of Example 2, indicating that the modified silica prepared by the method of the present invention effectively improves the dynamic properties of the tread rubber, effectively improves the anti-wet skid performance, and reduces its rolling resistance, while improving the tensile strength, elongation at break and wear resistance of the tread rubber.

[0138] In the present invention, after the white carbon black is preliminarily modified by mercaptoalkanoic acid, it reacts with solution polymerized styrene-butadiene rubber, and the white carbon black is bonded with the rubber molecular chain to obtain the modified white carbon black, and the dispersibility of the modified white carbon black is greatly improved, and the modified white carbon black can be closely combined with the rubber matrix, reducing the energy dissipation under dynamic load. Compared with the traditional white carbon black modified by silane coupling agent, the modified white carbon black prepared by the two-step method of the present invention avoids the aggregation of white carbon black and the delayed vulcanization of rubber materials caused by unstable dispersion, effectively improves the dynamic performance of the tread rubber, improves the anti-wet skid performance, reduces its rolling resistance, and also improves the tensile strength and elongation at break of the tread rubber.

[0139] As can be seen from Table 2, the Akron wear volume of the tread rubber of Comparative Example 2 is significantly higher than that of Example 2, and the tensile strength and elongation at break are significantly lower than those of Example 2, indicating that compared with the composite filler simply mixed, the composite filler prepared by ball milling and high-speed homogenization can significantly improve the wear resistance, tensile strength and elongation at break of the tread rubber;

[0140] The present invention uses nano silicon nitride, nano silicon carbide and graphite for pre-compounding by ball milling, and then forms a composite filler by high-speed homogenization, which helps to disperse the nano silicon nitride, nano silicon carbide and graphite pre-compound in the rubber, so that a stronger interface interaction is generated between the composite filler and the rubber, thereby improving the wear resistance, tensile strength and elongation at break of the tread.

[0141] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A wear-resistant tire tread rubber, characterized in that: The tread rubber comprises the following components in parts by weight: 40-60 parts of natural rubber, 25-35 parts of styrene-butadiene rubber, 15-25 parts of isoprene rubber, 25-30 parts of modified white carbon black, 20-25 parts of composite filler, 15-20 parts of N330 carbon black, 2-3 parts of stearic acid, 1-2 parts of calcium oxide, 1-2 parts of zinc oxide, 2.5-3.5 parts of antioxidant 4020, 8-12 parts of environmentally friendly aromatic oil TDAE, 0.1-0.5 parts of polyimide, 1.2-2 parts of sulfur, 1-2 parts of accelerator TMTD, 0.5-1 parts of accelerator NOBS, and 1-3 parts of anti-reversion agent HTS; The preparation method of the modified white carbon black includes primary modification and secondary modification; The primary modification comprises mixing mercaptoalkanoic acid and ethanol to form a mixed liquid A, mixing white carbon black and ethanol to form a mixed liquid B, adding the mixed liquid B to an equal volume of the mixed liquid A, stirring and reacting at 70-85° C. for 4-6 hours, standing for 10-12 hours after the reaction is completed, and then filtering, washing, and drying to obtain the primary modified white carbon black; The secondary modification comprises adding tert-butyl peroxybenzoate and the primary modified white carbon black into a solution of styrene-butadiene rubber toluene, controlling the temperature to 85-100° C., ensuring that the reaction is carried out under a nitrogen atmosphere, stirring the reaction at 300-400 rpm for 6-10 hours, and then filtering, washing and drying to obtain the modified white carbon black; The preparation method of the composite filler comprises preparing a mixed liquid, preparing a wet composite filler, and drying; The mixed liquid is prepared by mixing nano silicon carbide, nano silicon nitride and graphite, adding ethanol-water mixed liquid for ball milling, and performing ultrasonic treatment after the ball milling to obtain the mixed liquid; The wet composite filler is prepared by dispersing N660 carbon black in an ethanol solution, homogenizing at a speed of 8000-12000 rpm for 10-20 min to obtain a carbon black solution, then adding the mixed liquid to the carbon black solution, homogenizing at a speed of 8000-12000 rpm for 12-18 min, and then filtering to remove the solvent to obtain the wet composite filler.

2. The wear-resistant tire tread rubber according to claim 1, characterized in that: In the first modification step, the stirring rate is 600-800 rpm.

3. The wear-resistant tire tread rubber according to claim 1, characterized in that: In the first modification step, the mercaptoalkanoic acid is one of 3-mercaptopropionic acid, 4-mercaptobutyric acid, and 5-mercaptovaleric acid; The mass ratio of mercaptoalkanoic acid to ethanol in the blended liquid A is (2-4): (10-40); The mass ratio of white carbon black to ethanol in the blended liquid B is (10-15): (70-100).

4. The wear-resistant tire tread rubber according to claim 1, characterized in that: In the secondary modification step, the mass ratio of tert-butyl perbenzoate, primary modified white carbon black, and solution polymerized styrene-butadiene rubber is (0.2-0.3): (12-16): (50-60); The mass ratio of the solution polymerized styrene butadiene rubber to toluene in the solution polymerized styrene butadiene rubber toluene is (50-60): (400-600).

5. The wear-resistant tire tread rubber according to claim 1, characterized in that: In the step of preparing the mixed liquid, the ball-to-material ratio during ball milling is (25-35):1, the rotation speed is 200-320 rpm, and the time is 4-6 hours; In the step of preparing the mixed liquid, the ultrasonic treatment time is 10-20 minutes, and the ultrasonic frequency is 30-40 kHz.

6. The wear-resistant tire tread rubber according to claim 1, characterized in that: In the step of preparing the mixed liquid, the volume fraction of ethanol in the ethanol-water mixed liquid is 60-80%; The mass ratio of the nano silicon carbide, nano silicon nitride, graphite and ethanol-water mixed liquid is (0.3-0.5): (0.1-0.2): (3-5): (70-90).

7. The wear-resistant tire tread rubber according to claim 1, characterized in that: In the step of preparing the wet composite filler, the mass ratio of N660 carbon black to ethanol in the carbon black solution is (5-9):100; The mass ratio of the mixed liquid to the carbon black solution is (15-25):

100.

8. The method for preparing the wear-resistant tire tread rubber according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: plasticating, banburying, sheeting, and vulcanization; In the mastication, natural rubber, styrene-butadiene rubber and isoprene rubber are masticated at 56-62° C. for 14-16 minutes, and then thinned 3-5 times to obtain a masticated rubber; The banburying comprises adding the plasticized rubber into a banburying device with an initial temperature of 65-75° C. and an initial rotation speed of 25-30 rpm, adjusting the rotation speed to 45-60 rpm after the plasticized rubber is added, mixing for 1-2 minutes, and then adding stearic acid, calcium oxide, zinc oxide, antioxidant 4020, environmentally friendly aromatic oil TDAE, and polyimide, and then mixing for 1-2 minutes, adding modified white carbon black, composite filler, and N330 carbon black, mixing for 12-14 minutes, discharging, and parking for cooling for 10-12 hours after discharging to obtain the banburying rubber; The sheeting process comprises adding sulfur, accelerator TMTD, accelerator NOBS, and anti-vulcanization reversion agent HTS to the internal rubber mixture, thinning through the mixture 4-6 times, controlling the processing temperature at 55-65° C., and cooling the sheeting for 14-18 hours to obtain a mixed rubber; The vulcanization is to vulcanize the mixed rubber at 150-160° C. for 20-25 minutes to obtain the tread rubber.

Citation Information

Patent Citations

  • A self-healing rubber composition for tires and its preparation method

    CN113502135B

  • A solid aircraft tire tread compound and its preparation method

    CN113929978B

  • Method for synthesizing homogeneous nano silicon carbide powder by burning

    CN101125653A

  • Preparation method for modified white carbon black tread rubber

    CN109181038A

Cited By

  • Semi-steel radial tire with low rolling resistance and wet skid resistance and preparation method of semi-steel radial tire

    CN120098349A

  • A low rolling resistance, anti-slip semi-steel radial tire and its preparation method

    CN120098349B